PENERAPAN KEBIJAKAN MANAJEMEN KESELAMATAN KERJA DI DALAM PERUSAHAAN - Wahyuningsih, Sri (IKIP Gunungsitoli, 2009)
Abstract: This article study Â about factors causing the accident of activity, affect to company in the event of accident of activity, and also how effort able to be conducted by company to prevent of the accident of activity.Kata Kunci : management, work safety, company